KARAKTERISASI KONDISI KIMIA-FISIKA LINGKUNGAN PADA TINGKATAN DENSITAS MANGROVE YANG BERBEDA DI AMPALLAS, KABUPATEN MAMUJU, SULAWESI BARAT - Isyrini, Rantih; Werorilangi, Shinta; Mashoreng, Supriadi; Faizal, Ahmad; Tahir, Akbar; Rachim, Rastina (Hasanuddin University, 2017)
Mangroves have numerous ecological functions as well as economical values. In order to achieve successful of mangrove restoration and regain its functions, understanding on the factors affecting the establishment of mangroves are required. This study examined the characteristics of physico-chemical factors from three compartments (sediment, interstitial and seawater) that associated with different mangrove densities in Ampallas, District of Mamuju, West Sulawesi. The Principal Component Analysis and Spearman correlation analysis showed that high densities of adult and seedling mangroves strongly correlated to higher organic contents, dissolved oxygen of interstitial water, seawater salinities and lesser pH of sediments, seawater and interstitial. The reverse conditions applied for the less mangrove densities and control site that had no mangrove. In most cases, there were reciprocal relationships amongst the studied variables.Keywords: chemical-physical factors, density, mangroves.